A review of research on 360-degree video and its applications to education. Issue 5 (1st December 2022) - Shadiev, Rustam; Yang, Liuxin; Huang, Yueh Min
Abstract: 360-degree video is an emerging technology that creates virtually authentic learning environment. It has received considerable attention in the last few years. Nevertheless, not many scholars have reviewed research articles on this technology and its applications in education. This study intends to address this gap. To this end, fifty-two research articles published in the last five years on 360-degree video and its applications in the field of education are reviewed. The study focuses on (1) the tools used in the reviewed research, (2) the theories that were used to frame reviewed research, (3) the methodology used to collect the data, and (4) the findings reported in the reviewed research. In this study, we report the results and make several implications and suggestions for educators and researchers in the field. Supplemental data for this article is available online at https://doi.org/10.1080/15391523.2021.1928572 .